Submarine landslides and canyons: slope degradation and shelf-edge indentation in a tectonically active margin (Finale Basin, Northern Sicilian Margin, Tyrrhenian Sea) - Gamberi, F.; Scacchia, E.; Ferrante, V. (Frontiers in Earth Science, 2026)
Submarine canyons and landslides are closely related geological features of continental margins. They prevail on the continental slope and often reach the shelf edge, indenting the continental shelf. The character of the linkage between submarine canyons and landslides varies depending on their geological and geodynamic setting. Consequently, a wide range of geomorphologies and processes develops in association with landslides and canyons. They reflect different evolutionary pathways that ultimately lead to continental margin degradation. The latter is studied in our article through the analysis of multibeam bathymetric data and seismic lines in the Finale Basin in the northern Sicilian Margin. We identify landslides with complex histories and characters, with their main scarps located on the slope or indenting the shelf edge, often associated with debris flows. More importantly, we infer that depending on the landslide’s style, two types of canyons develop. “Worm canyons” nucleate in the lower slope and develop through successive small rotational slides migrating upslope along narrow corridors. “Racket canyons” develop in the depressions created by larger rotational slides in the upper slope and evolve through further downslope excavation due to debris-flow processes. Both canyon types can result in shelf-edge indentations. The latter are sometimes enhanced by duck-foot bowls, triangular depressions that form in the upper reaches of some of the canyons. The observations in our study area suggest that the northern Sicilian Margin is responding to out-of-grade conditions through canyon and landslide formation due to continental margin uplift and tilting. We highlight that canyon nucleation can occur in either the lower or the upper slope. We also show that, regardless of canyon type, debris flows are the most important processes for slope excavation, canyon enlargement, and canyon propagation. Finally, we observe a hierarchical pattern in the development of the elements and processes that lead to shelf-edge indentation. Relatively large indentations form coincidentally with a canyon-generating landslide; smaller indentations relate to bowl-shaped source areas of channelized debris flows.